AN OVERVIEW OF THUNDERSTORMS OVER BANGLADESH - Hoque, M Mozammel; Ahmed, S Jamal; Mallik, M A K; Hassan, SM Quamrul (Bangladesh Journal of Physics, 2025)
An attempt has been made to find out the monthly, seasonal and annual variability, and trend of thunderstorms (TSs) over Bangladesh, specialty the pre-monsoon TSs which are locally known as Nor’westers or Kal-baishakhis. TSs data for the period of 1981-2020, collected from Bangladesh Meteorological Department (BMD), have been analyzed and found that during this period average annual TS days were 66 having maximum in May and minimum in December. Seasonal distribution of TSs shows that highest and lowest number of TSs occurred in the monsoon season and winter season respectively but the pre-monsoon TSs are severe in nature. From the seasonal time series of TSs, it is seen that all the three seasons have increasing trend and the winter season shows decreasing trend. Station-wise distribution of annual average TS days reveals that Sylhet and Srimangal experience the highest number of TS days (136.28 and 116.92 days respectively), while Teknaf experiences the lowest number of TS days (26.15 days) during the study period (1981-2020). Spatial distribution of average annual and seasonal TS days shows that, the North-eastern part of the country is the most TS prone area, followed by northern, mid-western and north-western parts of the country. South-eastern part of the country experienced comparatively lower number of annual average TSs days. Most of the Nor’westers directed from north-west and occurred between 1400- 1600 U.T.C. and least number of Nor’westers occurred between 0400-0600 U.T.C. As the number of observatories of Bangladesh Meteorological Department (BMD) is less considering its area, there is possibilities of unnoticed thunderstorms over Bangladesh. Bangladesh Journal of Physics, Vol. 29, Issue 1, pp. 1 – 11, June 2022